Implementasi Pendidikan Sebaya dalam Pembelajaran Kelompok Minat di TMI Al-Amien Prenduan - Amar Ma’ruf, Ach. Nurholis Majid, Abd Haris, Abdul Munib (Universitas Islam Madura, 2021)
The success of schools as a sub-system of educational organizations can be seen from how the learning process can involve all components in education like teachers and student in onder to build good patterns of interaction. There are still many educational processes that are not in accordance with the real ideals of education today. There are still many teachers who underestimate the abilities of their students, as a result, many students or students whose abilities are still selected based on their respective intelligence. Thus, the process of transferring knowledge that should be running in education often experiences gaps between teachers and students. So the use of peers as tutors in learning can be an alternative to help students who experience learning difficulties if guided by their teacher. TMI Al-Amien Prenduan is an educational institution that implements peer education in the interest group learning sector. Learning language development, scouting, sports and so on are educational activities carried out by TMI Al-Amien Prenduan students with administrators (students in grades V and VI) as the tutors. This study will describe the models and methods of peer education applied in interest group learning at TMI Al-Amien Prenduan. The method used in this research is to use descriptive qualitative methods and case studies as the approach. Data collection techniques and data analysis techniques From this research, it can be concluded that peer education at TMI Al-Amien Prenduan is carried out by senior students in the learning process in extracurricular activities, including the development of foreign languages. Then the peer education method used at TMI Al-Amien Prenduan, especially in language development, is to provide practice questions regarding Arabic and English (at-Tamrin al-Lughawi), vocabulary enrichment (tazwidu al-mufradat), dialogue (hiwar ), and write papers in Arabic or English (insya ').